2022
DOI: 10.31609/jpmrs.2022-91405
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship Between Oral Motor Functions and Malnutrition in Children with Cerebral Palsy

Abstract: ÖZET Amaç: Serebral palsili (SP) çocuklarda beslenme problemleri ve malnütrisyon sıklıkla karşılaşılan sorunlardan biridir. Bu çalışma, SP tanısı almış çocuklarda sık görülen oromotor disfonksiyonlar ile malnütrisyon durumları arasındaki ilişkinin belirlenmesi amacıyla yürütülmüştür. Gereç ve Yöntemler: Araştırmaya 3-18 yaş arasındaki 55 SP tanısı almış çocuk dâhil edildi. SP'li çocukların kaba motor fonksiyon seviyeleri, kaba motor fonksiyon sınıflandırma sistemi (KMFSS) ile sınıflandırıldı. Çocukların yaşa v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…There have been many studies in the literature on the factors that cause feeding problems in children with CP [10][11][12]. Taş revealed that feeding behavior problems increased with worsening gross motor skills in children with CP aged 2-15 years [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many studies in the literature on the factors that cause feeding problems in children with CP [10][11][12]. Taş revealed that feeding behavior problems increased with worsening gross motor skills in children with CP aged 2-15 years [10].…”
Section: Introductionmentioning
confidence: 99%
“…Taş revealed that feeding behavior problems increased with worsening gross motor skills in children with CP aged 2-15 years [10]. Kürklü, in his study on children with CP aged 3-18, concluded that swallowing and chewing difficulties are associated with oral-motor insufficiency and that this is the most important cause of feeding problems [11]. Kangalgil, on the other hand, stated that behaviors such as keeping food in the mouth, choking while feeding, and food refusal are factors that cause feeding problems in children with CP aged 7-17 [12].…”
Section: Introductionmentioning
confidence: 99%